1999
DOI: 10.1001/jama.281.17.1638
|View full text |Cite
|
Sign up to set email alerts
|

Large-Core Needle Biopsy of Nonpalpable Breast Lesions

Abstract: Image-guided LCNB is a reliable diagnostic alternative to surgical excision of suspicious nonpalpable breast abnormalities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

12
90
3
5

Year Published

2001
2001
2014
2014

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 233 publications
(110 citation statements)
references
References 22 publications
12
90
3
5
Order By: Relevance
“…The specimen radiogram taken after the biopsy shows the area where the SVC was performed and verifies the correct positioning of the biopsy needle (microcalcification, asymmetrical density, etc.). The occurrence rate for microcalcifications observed in specimen radiograms following SVC biopsies has been reported as 95-100% (Meyer et al, 1999). In our study, specimen radiograms taken after SVC demonstrated that samples had been taken from the correct target points.…”
Section: Discussionsupporting
confidence: 53%
“…The specimen radiogram taken after the biopsy shows the area where the SVC was performed and verifies the correct positioning of the biopsy needle (microcalcification, asymmetrical density, etc.). The occurrence rate for microcalcifications observed in specimen radiograms following SVC biopsies has been reported as 95-100% (Meyer et al, 1999). In our study, specimen radiograms taken after SVC demonstrated that samples had been taken from the correct target points.…”
Section: Discussionsupporting
confidence: 53%
“…Similar to this last problem is the diagnosis of atypical duct hyperplasia in a core biopsy with subsequent upgrade to DCIS. 11,[27][28][29] These are all problematic because the differentiation is based on either the size or extensiveness of the lesion; and in a core biopsy, sampling error and size estimation is a built-in limitation. These are significant as the treatment methods differ between the different differentials.…”
Section: Discussionmentioning
confidence: 99%
“…Technical advances in percutaneous core needle biopsy, such as increasing needle diameter from 14-gauge to 11-gauge and adding a vacuum device, have allowed larger samples of tissue to be obtained (5,6), substantially improving the accuracy of diagnosis. Despite these improvements, the rate of underestimation for ADH has been reported as 10% to 26% for 11-gauge vacuum-assisted biopsy (VAB) (2,14,(21)(22)(23)(24)(25)(26)(27)(28). In this study, 11-gauge SVAB was associated with a lower rate of underestimation for ADH (20.6%), compared to USguided 14-gauge automated biopsy (41.7%) (P = 0.007).…”
Section: Discussionmentioning
confidence: 86%